Analysis of the rhizosphere bacterial diversity of Angelica dahurica var. formosana from different experimental sites and varieties (strains) - Jiang, Meiyan; Yao, Fei; Yang, Yunshu; Zhou, Yang; Hou, Kai; Chen, Yinyin; Feng, Dongju; Wu, Wei (PeerJ, 2023)
Background Rhizosphere bacteria play important roles in plant growth and secondary metabolite accumulation. Moreover, only with favorable production areas and desirable germplasm can high-yield and high-quality medicinal materials be produced. However, whether origin and germplasm indirectly affect the yield and quality of Angelica dahurica var. formosana through rhizosphere bacterial effects are not known. Methods In this study, a high-throughput sequencing strategy was used to explore the relationship between the rhizosphere bacterial community and the cultivation of A. dahurica var. formosana from different production areas and germplasm for the first time. Results (1) Proteobacteria was the dominant bacterial phylum in the rhizosphere soil of A. dahurica var. formosana, and these bacteria were stable and conserved to a certain extent. (2) High abundance of Proteobacteria was an important rhizospheric indicator of high yield, and high abundance of Firmicutes was an important indicator of high quality. Proteobacteria and Firmicutes might have an important relationship with the yield and quality of A. dahurica var. formosana, respectively. (3) PCoA cluster analysis demonstrated that both production area and germplasm affected the bacterial community structure in the rhizosphere of A. dahurica var. formosana to a certain extent, and production area had the greatest effect. In addition to available potassium, the rhizosphere soil nutrient levels of different production areas strongly affected the bacterial diversity and community. These findings provide a theoretical basis for the exploitation and utilization of rhizosphere microbial resources of A. dahurica var. formosana and offer a novel approach for increasing the yield and quality of this crop.
Keywords: Angelica dahurica; Rhizosphere bacteria; Production area; Germplasm